Prevalence of Plasmodium falciparum infection in school-aged children in urban and peri-urban schools of Bamako, Mali - Toure, Mahamoudou; Kane, Fousseyni; Sanogo, Daouda; Keita, Soumba; Keita, Bourama; Aro, Abdoul Zamilou; Keita, Moussa; Konate, Drissa; Diawara, Sory I.; Yaro, Alpha S.; Kone, Aissata; Magassa, Mahamadou; et al. (Frontiers in Malaria, 2025)
BackgroundUrban malaria is an increasing public health issue for Africans in cities experiencing rapid demographic growth. School children bear the high burden of malaria, which affects their health and education; however, they are not covered by control strategies such as seasonal malaria chemoprevention. This study aims to evaluate the school-based prevalence of Plasmodium falciparum infection to inform targeted malaria control strategies in urban and peri-urban settings of Bamako, Mali.MethodsThe city of Bamako in Mali was divided into four ecological strata based on the risk for malaria transmission using GIS tools (urban center, high altitude, riverside, and peripheral neighborhoods). Within each stratum, three schools close to the community health center were chosen to randomly select 200 to 230 children aged 6 to 13 years old per school to collect information on malaria risk factors and test for P. falciparum infection using malaria rapid diagnostic tests (mRTDs) and microscopy.ResultsOverall, the prevalence of P. falciparum infection varied from 0% to 15.5% between study sites. Travel history and fever were not associated with an increased risk of infection (p > 0.05). The odds of malaria infection increased by 2.4 among children with anemia (OR = 2.38, 95% CI = 1.57, 3.61) and 3.8 among children living in an urban site along the Niger River (OR = 3.37, 95% CI = 2.05, 7.45).ConclusionThis study shows significant spatial variation of P. falciparum infection within Bamako urban settings. The results suggest that, as in rural villages of Mali, school-aged children should be considered a major malaria parasite reservoir in the urban settings of Bamako. Interventions targeting this specific age group could reduce the malaria burden in this area.